2004
DOI: 10.1590/s1516-89132004000300015
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the morphometry of Macrobrachium nobilii (Decapoda, Palaemonidae)

Abstract: Fourteen morphometric characters of Macrobrachium nobilii (Henderson and Matthai, 1910), a freshwater prawn were measured from 72 males and 66 females collected at random in field. The growth constant (b) of total length and weight for male (4.28) and female (3.02) differed significantly (P<0.05). Comparison of slopes and elevations of regressions between sexes indicated significant difference in all the studied dependent parameters with carapace length (X), except with carapace width (Y). In males, major and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…Specimens with missing or regenerating limbs were excluded. In the present study, the carapace length (CL) was used as a reference dimension because it was the easiest, fastest and most reliable length measurement to obtain (Grandjean et al, 1997;Mariappan and Balasundaram, 2004).…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…Specimens with missing or regenerating limbs were excluded. In the present study, the carapace length (CL) was used as a reference dimension because it was the easiest, fastest and most reliable length measurement to obtain (Grandjean et al, 1997;Mariappan and Balasundaram, 2004).…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…Morphological characters, selected on the basis of inter-individual consistency and easy measurement, including 10 morphometric and 2 meristic traits (Table 1) were determined following description given by Lindenfelser (1984) and Mariappan & Balasundaram (2004). The traits included were rostrum length (ROSTRUM) and rostrum serration both on the dorsal (DORSER) and the ventral side (VENSER), carapace length and width (CARALENGTH and CARAWIDTH); length and maximum width of the abdomen (ABDLEN and ABDWID); length of the first pereiopod and that of its propodus (FSTLEG and PROP); length and maximum width of the telson (TELLEN) and (TELWID); and length of the antennal scale (ANTSCALE).…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…Although Kapiris and Thessalou-Legaki (2001) found the rostrum variability to be correlated to sex, maturity and size, Burukovsky (1972) reported that several shrimp species show strong rostral variability regarding different types of habitats. On the other hand, morphometric characters, such as the height of the abdominal somites, have been related to sex, due to special formations of the caridean female pleon for reproductive purposes (Schram 1996;Mariappan and Balasundaram 2004).…”
Section: Discussionmentioning
confidence: 99%